The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/srep36838
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of carbon nanotube to activate Subtilisin Carlsberg in polar and non-polar organic media

Abstract: In the work, we mainly used molecular dynamics (MD) simulation and protein structure network (PSN) to study subtilisin Carlsberg (SC) immobilized onto carbon nanotube (CNT) in water, acetonitrile and heptane solvents, in order to explore activation mechanism of enzymes in non-aqueous media. The result indicates that the affinity of SC with CNT follows the decreasing order of water > acetonitrile > heptane. The overall structure of SC and the catalytic triad display strong robustness to the change of environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…CNT surfaces were also used in order to understand the enzyme activation mechanism in non-aqueous media. The subtilisin carlsberg (SC) enzyme was immobilized onto CNT using water, acetonitrile and heptane as solvents ( Zhang et al, 2016 ). It was found that the affinity of SC on CNT decreases with acetonitrile and in more degree with heptane, in contrast to water.…”
Section: Immobilization On Graphene Oxide and Carbon Nanotubementioning
confidence: 99%
“…CNT surfaces were also used in order to understand the enzyme activation mechanism in non-aqueous media. The subtilisin carlsberg (SC) enzyme was immobilized onto CNT using water, acetonitrile and heptane as solvents ( Zhang et al, 2016 ). It was found that the affinity of SC on CNT decreases with acetonitrile and in more degree with heptane, in contrast to water.…”
Section: Immobilization On Graphene Oxide and Carbon Nanotubementioning
confidence: 99%
“…To estimate the binding energy between lysozyme and Gd@C 60 and their components, we carried out a MM-GBSA analysis of the trajectory. This methodology has provided valuable information to estimate the interaction between proteins and carbon nanomaterials. …”
Section: Results and Discussionmentioning
confidence: 99%
“…The escape barrier from the binding site is ~21 kcal/mol as calculated via the umbrella sampling method, in good agreement with the MMPBSA result. MMPBSA was also used in the theoretical design of the cyclic lipopeptide nanotube as a molecular channel in the lipid bilayer (Izadyar et al, 2015 ; Khavani et al, 2015 , 2017 ), in the study of the enzyme immobilization mechanism of alpha-chymotrypsin onto carbon nanotubes in organic media (Zhang L. Y. et al, 2015 ), and the mechanism of carbon nanotube activation of subtilisin Carlsberg in polar and non-polar organic media (Zhang L. Y. et al, 2016 ).…”
Section: Applications Of Mmpbsamentioning
confidence: 99%